Examining neighborhood and interpersonal norms and social support on fruit and vegetable intake in low-income communities - Akilah Dulin; Patricia M. Risica; Jennifer Mello; Rashid Ahmed; Kate B. Carey; Michelle Cardel; Chanelle J. Howe; Sarah Nadimpalli; Kim M. Gans (BMC Public Health, 2018)
Abstract Background We examined whether neighborhood-, friend-, and family- norms and social support for consumption and purchase of fruits and vegetables (F&V) were associated with F&V intake among low-income residents in subsidized housing communities. We examined baseline data from a study ancillary to the Live Well/Viva Bien intervention. Participants included 290 residents in four low-income subsidized housing sites who were ≥ 18 years of age, English and/or Spanish speaking, and without medical conditions that prevented consumption of F&V. Methods Linear regression models examined associations of norms and social support with F&V intake after adjustments for sociodemographic characteristics. Results In the analysis, neighborhood social support for F&V was associated with a 0.31 cup increase in F&V intake (95% CI = 0.05, 0.57). The family norm for eating F&V and family social support for eating F&V were associated with a 0.32 cup (95% CI = 0.13, 0.52) and 0.42 cup (95% CI = 0.19, 0.64) increase in F&V intake, respectively. Conclusions To our knowledge, no other studies have examined neighborhood, family, and peer norms and social support simultaneously and in relation to F&V intake. These findings may inform neighborhood interventions and community-level policies to reduce neighborhood disparities in F&V consumption.